Building the confidence of teachers to facilitate sexual and reproductive health information to in-school youth clubs in Uganda - Tunusiime, Molly; Kaduyu, Paul; Kanakulya, Hassan; Mukisa, Rose (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To build the confidence of schoolteachers to provide sexual and reproductive health (SRH) information and empower in-school youth to make healthy and informed decisions. Methods: Using a 4-pointscale,school teachers reported their confidence discussing eleven SRH topics (e.g. adolescent development, characteristics of sexually healthy adolescents, adolescent pregnancy and prevention, and HIV/AIDS).Confidence was assessed before and after a 5-day training, and a year after implementing in-school SRH sessions. Results: Self-reported confidence rose for all items after training. For example, only35% of teachers were confident or very confident to discuss characteristics of sexually healthy adolescents or male sexual anatomy before training; this rose to 96% and 87%, respectively. Similarly, the percentage of teachers who felt confident/very confident to conduct sessions on adolescent pregnancy and HIV/ prevention rose from 39% to 96%. Conclusions: With appropriate training, secondary school teachers with limited SRH information can gain the confidence to disseminate accurate SRH information and help adolescents make informed SRH choices. This is crucial to promote SRH among Ugandan adolescents and support a fistula-free generation.